A Psycholinguistic Study on Expressive Language Disorder of Autistic Characters in Miracle Run Movie - Fitriatul Masitoh; Yogi Rohana (Universitas PGRI Yogyakarta, 2023)
Recently, it has been reported that the prevalence of autism has increased significantly. One of the characteristics of autism is a language problem, or it is well-known linguistically as a language disorder. This study is conducted to analyze categories of expressive language disorder of autism represented in Miracle Run Movie and contexts affecting them in producing those utterances. This study applies a descriptive qualitative approach using Carroll's framework (1985). As the result of analysis on 75 data, Philip and Steven, as the autistic characters, face all kinds of expressive language disorders covering phonology, syntax, semantics, and pragmatics in various cases. They face phonological language disorder in the case of inappropriate stress, flat and singsong intonation, and expressionless speech. They also face syntactical language disorder in the case of echolalia and semantic language disorder involving their disability in using semantic bias. In addition, they have pragmatic language disorder in the case of fewer complex gestures, politeness strategy, spontaneous remarks, misuse of pronouns, limited repertoire devices to initiate a topic in a conversation, and tendency to use a question to gain a response from a listener. Concerning the context when the autistic characters produce expressive language disorder, there are six types of context affecting their utterances. They have expressive language disorder when they are posing a question to someone, answering a question of others, expressing their ambition, expectation, surprise, and something they dislike. This study is an excellent guide for EFL teachers interested in working with autistic students.